Does the menstrual cycle and use of oral contraceptives influence the risk of low back pain? A prospective study among female soccer players - Brynhildsen, J. O.; Hammar, J.; Hammar, M. L. (Scandinavian Journal of Medicine & Science in Sports, 1997)
Female sex hormones have been suggested to affect the risk of low back pain. One reason is the fact that back pain is a very common symptom during pregnancy. It also seems to be a more common problem among female than male athletes, e.g. in soccer. Although there are few scientific data supporting a relationship between female sex hormones, use of oral contraceptives and low back pain, many doctors and physiotherapists advise women with low back pain to avoid oral contraceptives. The aim of this study was to evaluate whether low back pain fluctuated during the menstrual cycle and differed between women using and not using oral contraceptives. A questionnaire was sent to 12 female soccer teams; 261 players answered and 50 players (28 with back pain and 22 controls) fulfilled the prospective study. At baseline the players underwent a thorough clinical examination and then filled in a diary concerning menstrual data, back pain, training and matches during one season. A total of 296 menstrual cycles was analysed. No difference in prevalence or severity of back pain was seen between the different phases of the menstrual cycle or between users and non-users of oral contraceptives. Our data do not support the hypothesis that low back pain is influenced by hormonal fluctuations during the menstrual cycle or by use of oral contraceptives. Scand J Med Sci Sports 1997 Dec;7(6):348-53